Borehole thermal energy storage systems under the influence of groundwater flow and time-varying surface temperature. (March 2017) - Nguyen, A.; Pasquier, P.; Marcotte, D.
Abstract : Highlights: A new numerical model to generate transfer functions for borehole thermal energy storage system. The model includes the effect of groundwater temperature variations, ground surface temperature variations and groundwater flow. A spectral approach is proposed to generate the outlet fluid temperature of the system. The spectral approach is fast and efficient. Abstract: A 3D finite element model of circular borehole cluster connected in series is used as a response model to generate normalized transfer functions of a borehole thermal energy storage system under the influence of ground surface temperature variations and groundwater flow. Two response functions are obtained by convolving transfer functions of the system's outlet fluid temperature with two incremental input functions describing the temperature variation of the inlet and outlet fluid and variations of the ground surface temperature. Superposition is applied to obtain the resulting fluid temperature with respect to thermal inputs at the inlet fluid and the ground surface over the course of ten years and results are compared for various groundwater velocities. This work demonstrates that the combined effect of groundwater flow and ambient air temperature variations can significantly decrease the performance of a BTES system. The methodology used can be extended to simulate complex system.